Installation of precast wall panel on site - Roslan, Muhammad Najmi (Universiti Teknologi MARA, Perak, 2019)
Industrialised Building System (IBS) and is one of construction system used by Malaysia. This system is a product manufactured from the factory for installation on site. The aim of this study is to explore the installation method of precast wall panel installation on site at Masai, Johor. Besides, to determine the problem occurred during the construction. Data was collected during the observation and document review. In addition, Interview with site supervisor on wall panel system construction techniques. Moreover, conventional method also has been used for this building, this can conclude Industrialised Building System are new industry transformation for Malaysia.